Implementing the Principles of Effective Governance for Sustainable Development (African Journal of Public Administration & Management, 2026)
To promote government that is responsive to the needs and aspirations of all people, central authorities should perform only those tasks which cannot be performed effectively at a more intermediate or local level. Strategy guidance notes have been produced by DESA/DPIDG and UNPOG
Keywords: Principles of Effective Governance; Sustainable Development